Gaya Kepemimpinan Kepala Sekolah dalam Mewujudkan Merdeka Belajar di SMA Negeri Pemana - Nur Hidayah; Sunarwin, Sunarwin; Aloisius Harso (Jurnal Bersama Ilmu Pendidikan (DIDIK), 2025)
Principal leadership is the ability to mobilize existing resources in a school which will be used optimally to achieve the expected goals. In this study, the main objective is to realize independent learning at SMAN Pemana under his leadership. Independent Learning is a program launched by the Minister of Education, Culture, Research, and Technology of the Republic of Indonesia. Independent Learning is an educational development concept where all stakeholders are expected to become agents of educational change. The role of the principal in leadership has a significant impact on improving teachers and all sudents at SMAN Pemana in realizing the independent learning that is applied. In this study, the researcher used a qualitative approach with a descriptive method to collect data such as: (1) the principal's leadership style in improving work discipline, (2) the principal's leadership style in realizing independent learning, (3) obstacles faced by the principal in realizing independent learning at SMAN Pemana. The researcher collected data through interviews, observations